Multi-measure assessment of adherence to antiretroviral therapy among children under five years living with HIV in Jinja, Uganda - Jacquellyn Nambi Ssanyu; Mary Nakafeero; Fred Nuwaha (BMC, 2020)
Abstract Background Adherence to Antiretroviral Therapy (ART) is required to achieve HIV viral load suppression. However, children under 5 years in Jinja, Uganda, had been shown to have low HIV suppression rates. This study aimed to determine the level of ART non-adherence among these children and the associated factors. Methods Data for the cross-sectional study was collected from April to July 2019, from caregivers of 206 children under 5 years living with HIV who were attending health facilities in Jinja and had been on ART for at least 3 months. Non-adherence was measured using a Visual Analog Scale that assessed both dosing and timing non-adherence, and by determining the Proportion of Days Covered by the medication. A questionnaire administered to the caregivers was used to collect the data, together with medical record review. A child was only considered adherent if they had adherence greater than 95% on all the measures. The data was analysed using Modified Poisson Regression, taking a p-value less than 0.05 as statistically significant. Results Of the 206 children, 73.8% were older than 2 years, and 52.9% were female. Likewise, the majority of caregivers were female (93.7%). Using the combined adherence measure, 57.3% of the children were categorised as non-adherent. School/day-care attendance, Prevalence Ratio (PR) = 1.25 (p = 0.042), the caregiver having higher than a primary school education, PR = 0.72 (p = 0.044) and satisfaction with the quality of service at the health facility, PR = 0.97 (p < 0.001) were associated with non-adherence. Household food insecurity was also associated with non-adherence: PR = 1.55 (p = 0.011) for mild food insecurity, PR = 1.75 (p = 0.001) for moderate insecurity and PR = 1.48 (p = 0.015) for severe food insecurity. Conclusions Children under 5 years in Jinja had a high level of ART non-adherence. It is important to engage schools to support adherence among children living with HIV. Addressing household food insecurity and improving the quality of paediatric ART services would also reduce the barriers to optimal adherence.